FIGURATIVE LANGUAGE FOUN DIN CELINE DION ALBUM “FALLING IN TO YOU” BY CELINE DION - Yasimani Laia (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
This articel describes the kinds of figurative language in songs lyrics by The Figurative Languange Found in Celina Dion Album “Falling in to You” By Celina Dion. Language is one of the crucial tools for human beings. The scientific study of language is called linguistics. When we study linguistics, we delve into semantics, which includes the study of figurative language. The objective of this study is to identify the types of figurative language in the lyrics of songs from the album "Falling Into You" and to describe the figurative meaning of each type of figurative expression found in the lyrics. The researcher uses a descriptive qualitative method to analyze and classify every line of the song lyrics. The data source used by the researcher comprises ten songs from the album "Falling In to You": “Falling Into You,” “It’s All Coming Back to Me Now,” “Because You Loved Me,” “Make You Happy,” “Seduces Me,” “All by Myself,” “Declaration of Love,” “I Love You,” “Dreamin’ of You,” and “River Deep, Mountain High.” After analyzing and investigating every line in the song lyrics, the researcher found several instances of figurative language. There are nine types of figurative language used in the lyrics: 15 metaphors, 6 personifications, 3 apostrophes, 9 similes, 4 metonymies, 5 synecdoches, 6 understatements, 1 paradox, and 5 hyperboles. The dominant figurative language used is metaphor. The meaning of figurative language in the lyrics of "Falling In to You" goes beyond their literal meanings as found in dictionaries. Based on the data analysis, the researcher found that the songwriter uses these expressions to convey feelings, emotions, and phenomenal events, making the songs more interesting and engaging for listeners.